2021
DOI: 10.3390/ijms22179174
|View full text |Cite
|
Sign up to set email alerts
|

A SmelAAT Acyltransferase Variant Causes a Major Difference in Eggplant (Solanum melongena L.) Peel Anthocyanin Composition

Abstract: Eggplant berries are rich in anthocyanins like delphinidin-3-rutinoside (D3R) and nasunin (NAS), which are accumulated at high amounts in the peel. NAS is derived by D3R through acylation and glycosylation steps. The presence of D3R or NAS is usually associated with black-purple or lilac fruit coloration of the most cultivated varieties, respectively. Building on QTL mapping position, a candidate gene approach was used to investigate the involvement of a BAHD anthocyanin acyltransferase (SmelAAT) in determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…In addition, several studies evaluated the effect of genetic and physiological factors on anthocyanin accumulation in eggplant. This led to the identification of several quantitative trait loci and selective sweeps related to anthocyanin content (Barchi et al, 2012(Barchi et al, , 2021Cericola et al, 2014;Florio et al, 2021;Toppino et al, 2016), and revealed that both light and temperature treatments affect anthocyanin content in eggplant (Jiang et al, 2016;Zhang et al, 2019). Except for the recent discovery that a single-base deletion in SmelAAT, encoding an anthocyanin acyltransferase, causes a major difference in the anthocyanin composition, and thereby color, in several eggplant cultivars (Florio et al, 2021), it is still largely unknown whether and how variation in structural genes of the anthocyanin biosynthetic pathway affect anthocyanin accumulation patterns in eggplant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies evaluated the effect of genetic and physiological factors on anthocyanin accumulation in eggplant. This led to the identification of several quantitative trait loci and selective sweeps related to anthocyanin content (Barchi et al, 2012(Barchi et al, , 2021Cericola et al, 2014;Florio et al, 2021;Toppino et al, 2016), and revealed that both light and temperature treatments affect anthocyanin content in eggplant (Jiang et al, 2016;Zhang et al, 2019). Except for the recent discovery that a single-base deletion in SmelAAT, encoding an anthocyanin acyltransferase, causes a major difference in the anthocyanin composition, and thereby color, in several eggplant cultivars (Florio et al, 2021), it is still largely unknown whether and how variation in structural genes of the anthocyanin biosynthetic pathway affect anthocyanin accumulation patterns in eggplant.…”
Section: Introductionmentioning
confidence: 99%
“…Solyc05g010180.3.1 (Log 2 Fc = −2.22; tomato carotenoid isomerase CRTISO ) is involved in carotenoids biosynthesis. In MicroTom fruits, the downregulation of carotenoid isomerase has been demonstrated to induce an accumulation of zeta-carotene and cis -prolycopene ( dos Santos et al, 2017 ; Florio et al, 2021 ), both elevating and modifying carotenoid profiles toward more bioavailable forms compared to wild-type ( Pelletier et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, the delphinidins were reported as the main anthocyanins in purple plants’ peels ( Liang et al, 2022 ; Wang et al, 2021 ). In purple eggplant peels, delphinidin 3-O-glucoside ( Yang et al, 2022 ), delphinidin-3-rutinoside (D3R) ( Florio et al, 2021 ), delphinidin-3-(p-coumaroylrutinoside)-5-glucoside ( Azuma et al, 2008 ) and delphinidin 3-O-rutinoside ( Condurache et al, 2021 ) were enriched. They all belonged to the delphinidin though their structure were different.…”
Section: Discussionmentioning
confidence: 99%